CERIA: A Community Empowerment as Dementia Preventive Measure among Elderly - Afidjati, Hera; Ronoatmodjo, Sudarto; Muharrom, Muhammad Aji; Deslanthy, Belinda Thania; Khaerani, Ayu Suciah; Adre Mayza (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Dementia is predicted to double in the next 15 years and causes adverse socioeconomic effects, yet the clinical therapy for dementia has not shown satisfactory results for many years. Preventive efforts involving the active role of the elderly and supported by the development of information technology are strongly needed. Method: This is a quasi-experimental study aimed to evaluate the effectiveness of CERIA as community-based intervention and to increase the awareness of dementia. CERIA (Cerdas Hindari Demensia) was implemented for 32 elderlies in Pasar Minggu District, South Jakarta who were willing to participate. The interventions implemented were memory training, brain vitalization gymnastics, playing angklung, and storytelling to toddlers. We measured the pre-and post-intervention scores of the elderly using an assessment tool of dementia screening, then compared the results using Student T-test. We also created a dementia prevention manual book (Buku Panda) and built a smartphone app for educational purposes. Results: As many as 97% of the elderly have a good daily activity score and 90.9% have a good body balance. Assessment of pre-intervention cognitive function showed a mean value of 27 and increased to 29 after intervention. The pre-intervention emotional assessment showed a mean value of 1 and decreased in post-intervention to 0. Some of the most afflicted diseases of the elderlies were hypertension (30,3%) and diabetes mellitus (18,2%). Conclusion: This dementia prevention program has a strong potential to be implemented in wider scope. Further improvement involving parties such as the Ministry of Health is needed to replicate this effort.